2017
DOI: 10.5152/cjms.2016.167
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Continuous Systemic Inflammation in Pregnant Women with Hyperemesis Gravidarum

Abstract: BACKGROUNDTo evaluate the serum inflammatory markers in the first trimester in which hyperemesis gravidarum (HG) usually occurs and in the late second trimester when symptoms of HG usually resolve. MATERIALS and METHODSThe study population consisted of 170 pregnant women with HG and 185 healthy gestational-age-matched controls. White blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) were compared during the first and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 21 In a prospective study including 355 pregnant women, the WBC, NLR, PLR, and RDW were found to be higher in the HG group, and even in the late second trimester of pregnancy, they remained high in patients with HG. 22 A study by Çintesun et al 23 demonstrated that the NLR and PLR were effective markers in HG. In agreement with the literature, the NLR and PLR were high in patients with HG in the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In a prospective study including 355 pregnant women, the WBC, NLR, PLR, and RDW were found to be higher in the HG group, and even in the late second trimester of pregnancy, they remained high in patients with HG. 22 A study by Çintesun et al 23 demonstrated that the NLR and PLR were effective markers in HG. In agreement with the literature, the NLR and PLR were high in patients with HG in the present study.…”
Section: Discussionmentioning
confidence: 99%